SOME UNUSUAL SOLUTIONS FOR EUROPEAN NETWORKS - Vernescu V; Goia M.L.; Golovanov N. (Problems of the Regional Energetics, 2012)
Authors present several non-conventional solutions unused in Europe which are, however, frequently adopted in some medium (M) and low (L) voltages (V) networks from North-American and Australian countries, especially in low density areas of consumption in rural and urban distribution. The proposed solutions may assure diversified supply possibilities in our middle and South–Eastern regions, as regards modernizing and upgrading the distribution networks. The solutions try to propose to adapt our European practice to the North-American experience, aiming at developing more flexible, cheaper and safer supply of the consumers, both at MV and at LV networks. Several original solutions promoted in Romanian networks and their peculiarities are also described. The paper presents distribution schemes at medium voltage in connection with low voltage supply in different condition of neutral treatment at MV or LV. It also shows the measures to be adopted in order to diminish the investment expenses in low voltage at the supplied consumers. The technical condition of co-existence of OHEL at MV and LV on the same poles, without jeopardizing the LV equipment, is necessary. Among the solutions proposed, the authors also describe the unconventional one, consisting in the supply of isolated monophase consumer at MV by ground return and also the conditions necessary for sure and safe operation of this particularly connection. Finally, there are shown some conclusions about the necessity to assure imposed environmental conditions.